Syngas Production From Palm Kernel Shells With Enhanced Tar Removal Using Biochar From Agricultural Residues† - Dechapanya, Wipawee; Rattanahirun, Suttipong; Khamwichit, Attaso (Frontiers in Energy Research, 2020)
In this study, palm kernel shells (PKS) were utilized in an air gasification process to produce syngas. Also, biochar prepared from pyrolysis of the mangosteen and durian peels was used in the process to enhance the tar removal efficiency. The expected outcomes of this study could result in not only the generation of renewable energy but also the waste utilization of agricultural residues. The effect of catalysts and biochar on tar reduction to improve the syngas quality were extensively studied. A downdraft gasifier equipped with catalytic and adsorption units was utilized to produce syngas. The process was operated with 1 kg of palm shell per batch at a fixed airflow rate of 25 L/min. The NiO/CaO catalysts with a fixed CaO amount of 10 wt% and various NiO contents of 2, 4, and 8 wt% were synthesized by co-impregnation on the ceramic supporter. The results of SEM analysis showed that the NiO and CaO were deposited and well dispersed on the porous ceramic supporters. The presence of an associated active NiO peak at a wavelength of 692 cm–1 was observed in the FTIR result. The durian and mangosteen peels residues were pyrolyzed at 400–600°C for 2 h to prepare biochar to be used as tar adsorbent. The BET surface area of obtained biochar was 0.9219–0.9989 m2/g with a range of adsorption pore size of 11.193–11.912 nm. The syngas samples were collected from the gasification unit at 15, 25, 35, 45, and 60 min during a 1-h period of processing time. The syngas compositions were analyzed by gas chromatography. The GC results indicated that increasing NiO contents in the catalysts tended to result in increasing methane and carbon dioxide concentration of the syngas, possibly contributed from the tar cracking reactions. With the presence of biochar, the amount of tar captured in the filter unit was significantly increased up to nine times compared to the system without biochar.